Helicobacter pylori eradication reduces risk for recurrence of gastric hyperplastic polyp after endoscopic resection - Cho, Young Sin; Nam, Su Youn; Moon, Hee Seok; Kim, Tae Ho; Kim, Sung Eun; Jung, Jin Tae (The Korean journal of internal medicine, 2023)
Background/Aims: Little is known about the effect of Helicobacter pylori eradication on the recurrence of gastric hyperplastic polyps after endoscopic resection. Thus, we evaluated the recurrence rate of gastric hyperplastic polyps based on H. pylori eradication following endoscopic resection.Methods: We retrospectively reviewed the medical records of 201 patients with H. pylori infection who underwent endoscopic resection for gastric hyperplastic polyps at six medical centers. H. pylori status was assessed by histological analysis and a rapid urease test. A total of 149 patients underwent successful H. pylori eradication (eradication group), whereas 52 patients had persistent H. pylori infections (non-eradication group). The recurrence rate of gastric hyperplastic polyps and the risk factors according to H. pylori status were analyzed.Results: During the mean follow-up period of 18.3 months, recurrent gastric polyps developed after endoscopic resection in 10 patients (19.2% [10/52]) in the non-eradication group and 12 patients (8.1% [12/149]) in the eradication group. The cumulative incidence of recurrent gastric hyperplastic polyps was significantly higher in the non-eradication group than in the eradication group (p = 0.041, log‐rank test). In the adjusted analysis, H. pylori eradication reduced the recurrence of gastric hyperplastic polyps (hazard ratio [HR], 0.42; 95% confidence interval [CI], 0.18 to 0.99), whereas anticoagulation therapy increased the risk of recurrence of gastric hyperplastic polyps (HR, 4.91; 95% CI, 1.39 to 17.28).Conclusions: Successful eradication of H. pylori may reduce the recurrence of gastric hyperplastic polyps in patients after endoscopic mucosal resection.